Reactive Power Contribution and Pricing for Restructured Power Industry - Susithra.M, nan; Gnanadass.R, nan (Iraqi Journal for Electrical and Electronic Engineering, 2015)
Competitive trend towards restructuring and unbundling of transmission services has resulted in the need renteto discover the impact of a particular generator to load. This paper initially presents the analysis of three diff reactive power valuation methods namely, Modified Y bus , Virtual flow approach and Modified Power flow tracing to compute the reactive power output from a particular generator to particular load. Among these methods, the modified power flow electricity tracing method is identified as the best because of its various features. Secondly, based on this Method, the opportunity cost for practical system is determined. Hence, this method can be useful in providing additional insight into power system operation and can be used to modify existing tariffs of charging for reactive power transmission loss and reactive power transmission services. Simulation and comparison results are shown by taking IEEE 30 bus system as test system.